علم الصرف، نظرياته وتطوراته والاستفادة منه في تعليم اللغة العربية - Akhsan Akhsan; Ahmadi Muhammadiyah; Wahyudin Wahyudin; Zulli Umri (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
Sharf is one of the most important branches of knowledge in Arabic, by which a learner can know and understand the form of a word, its origin, its changes, and its meaning, so that it is hoped that he will be able to understand the Arabic text he reads and hears. The substance of the Sharf is to discuss the forms of words with the aim of knowing the meaning of each of these word changes. The goal of learning Sharaf is to teach students about changes in the form of a word to another word to find out its true meaning. Sharf science is one of the scientific principles in Arabic which is one of the media (intermediaries) to master language skills. Therefore, the Sharf should be taught by paying attention to the following matters: 1) Teaching the Sharf science is not a goal (learning the science of Sharf for the Sharf) but as a instrumen (tool) to get competence and language skills, 2) Teaching the Sharf requires a lot of practice and not only focus on teaching the rules and forgetting the basic function, 3) it must be taught in stages according to the students' abilities, for example from Mujarrad to Mazid and practice in perfect sentences (Jumlah Mufidah).